Ancient Greek and Roman Art and Architecture. Volume 1, - Palagia, Olga (De Gruyter, 2019)
The Handbook of Greek Sculpture aims to provide a detailed examination of current research and directions in the field. Bringing together an international cast of contributors from Greece, Italy, France, Great Britain, Germany, and the United States, the volume incorporates new areas of research, such as the sculptures of Messene and Macedonia, sculpture in Roman Greece, and the contribution of Greek sculptors in Rome, as well as important aspects of Greek sculpture like techniques and patronage. The written sources (literary and epigraphical) are explored in dedicated chapters, as are function and iconography and the reception of Greek sculpture in modern Europe. Inspired by recent exhibitions on Lysippos and Praxiteles, the book also revisits the style and the personal contributions of the great masters.- Resumé vydavatel
Keywords: sochařství -- dějiny -- Řecko; sculpture -- history -- Greece; elektronické knihy; sborníky; electronic books; papers of several authors